Analisis Hubungan Orientasi Pasar dan Inovasi Produk Terhadap Keunggulan Bersaing pada UKM Kuliner di Kecamatan Medan Maimun - Alkadri, Ridho; Yunita, Nindya; Alfifto, Alfifto; Royani, Ida (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine "The Effect of Market Orientation and Product Innovation on Competitive Advantage in Culinary SMEs in Medan Maimun District". This type of research is associative. The population in this study were 117 culinary SMEs in Medan Maimun District using the Slovin formula technique, so the number of samples in this study was 53 respondents taken from part of the population. Based on the t results, it can be seen that the t count for the Market Orientation variable is 4.240> t table of 2.008 and the Product Innovation variable is 0.924 <t table of 2.008 with a probability of t, namely sig <0.05 for the Competitive Advantage variable. Based on the results of the F test, the F count value is 0.000 <0.05 for Market Orientation and 0.360> 0.05 for Product Innovation, indicating that Market Orientation has a positive and significant effect on Competitive Advantage and Product Innovation does not have a positive and insignificant effect on Competitive Advantage. The Adjusted R Square value obtained is 0.467 or 46.7% Competitive Advantage can be explained by Market Orientation and Product Innovation, the remaining 53.3% is influenced by other factors not explained in this study.